1999
DOI: 10.2307/2640720
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the Pantropical Sea Urchin Eucidaris in Relation to Land Barriers and Ocean Currents

Abstract: Abstract.-The pantropical sea urchin genus Eucidaris contains four currently recognized species, all of them allopatric: E. metularia in the Indo-West Pacific, E. thouarsi in the eastern Pacific, E. tribuloides in both the western and eastern Atlantic, and E. clavata at the central Atlantic islands of Ascension and St. Helena. We sequenced a 640-bp region of the cytochrome oxidase I (COI) gene of mitochondrial DNA to determine whether this division of the genus into species was confirmed by molecular markers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 38 publications
8
130
2
1
Order By: Relevance
“…regalis group (Banford et al, 1993). In general, however, our findings and those of others (Lessios et al, 1999(Lessios et al, , 2000Muss et al, 2001;Scheltema, 1973Scheltema, , 1995 do not fully support RosenÕs hypothesis for relationships of New World to eastern Atlantic faunas and the timing of these events. Specifically as an example, the relationship of S. timucu and S. senegalensis indicates a very recent separation of transAtlantic species and includes the possibility of dispersal playing a central role.…”
Section: Vicariance and Dispersal Across The Ep/ea Biogeographic Trackcontrasting
confidence: 85%
“…regalis group (Banford et al, 1993). In general, however, our findings and those of others (Lessios et al, 1999(Lessios et al, , 2000Muss et al, 2001;Scheltema, 1973Scheltema, , 1995 do not fully support RosenÕs hypothesis for relationships of New World to eastern Atlantic faunas and the timing of these events. Specifically as an example, the relationship of S. timucu and S. senegalensis indicates a very recent separation of transAtlantic species and includes the possibility of dispersal playing a central role.…”
Section: Vicariance and Dispersal Across The Ep/ea Biogeographic Trackcontrasting
confidence: 85%
“…Molecular phylogenies of regular echinoids (Lessios et al, 1999(Lessios et al, , 2001(Lessios et al, , 2003McCartney et al, 2000;Zigler and Lessios, 2004;Palumbi and Lessios, 2005) have agreed with Mayr's (1954) model of allopatric speciation. However, our data revealed that not all divergence highlighted in this study fits an allopatric model.…”
Section: Timing and Possible Causes Of Divergencementioning
confidence: 54%
“…However, one species of Mellita, M. grantii Mortensen, 1948, proved problematic for Mayr (1954) and he chose to ignore it in his analysis, stating that Mortensen (1948) had described M. grantii based on a single specimen from the midst of the range of M. longifissa Michelin, 1858. Mayr's (1954 model of allopatric speciation in echinoids has been supported by molecular phylogenies of regular sea urchins (Lessios et al, 1999(Lessios et al, , 2001(Lessios et al, , 2003(Lessios et al, , 2012McCartney et al, 2000;Zigler and Lessios, 2004;Palumbi and Lessios, 2005), but to-date this hypothesis has not been tested with a molecular phylogeny of a sand dollar genus.…”
Section: Introductionmentioning
confidence: 99%
“…Widespread occurrence of extant species, even on remote archipelagos (e.g., Drew, 1995;Hillis-Colinvaux, 1980Taylor, 1950;Tsuda and Kamura, 1991;Tsuda and Wray, 1977) and pan-tropical patterns of fossil ones prior to the vicariant events (Elliott, 1981;Fl€ u ugel, 1988) suggest long-distance dispersal. Such dispersal in marine organisms is considered to be a function of larval endurance in the plankton, active migrating or drifting capability, (ir)-regularity of ocean current patterns, seawater temperature tolerance limits, and habitat availability (seaweeds: Prud'homme van Reine and Van den Hoek, 1988, 1990Van den Hoek, 1987, corals: Veron, 1995, fish: Bowen et al, 2001Colborn et al, 2001;Muss et al, 2001, and sea urchins: Lessios et al, 1999Lessios et al, , 2001. Although calcified thalli of Halimeda are unlikely drifters, uncalcified juvenile stages, which grow slowly for extended periods (Meinesz, 1980), could hitchhike across the ocean on drift material (Woelkerling, 1975).…”
Section: Phylogeographymentioning
confidence: 99%